PELATIHAN KETERAMPILAN BERBAHASA INDONESIA UNTUK MENINGKATKAN PROFESIONALISME PARA SANTRI PONDOK PESANTREN MADRASTUL QUR’AN TEBUIRENG JOMBANG DALAM MENERJEMAHKAN TEKS BAHASA ARAB KE BAHASA INDONESIA YANG BAIK DAN BENAR DI ERA DIGITAL - Supratno, Haris; Subandiyah, Heny; Raharjo, Resdianto Permata; Indriyanti, Aries Dwi; Amalia Shofiani, Arisni Kholifatu (ABIDUMASY, 2024)
The purpose of this Community Service activity is to provide knowledge and skills to the students of Pondok Pesantren Madrasatul Qur'an Tebuireng Jombang which includes: (1) Indonesian spelling, (2) sentence writing, (3) translation techniques, and (4) skills in using computers in the translation process. The specific targets to be achieved are that the students can (1) translate Arabic text into Indonesian using good and correct Indonesian (2) can use computers in the process of translating Arabic text into good and correct Indonesian. The methods used were lectures, questions and answers, assignments, and practice translating Arabic text into Indonesian using a computer. The results of this PKM activity are that the students of Pondok Pesantren Madrasatul Qur'an Tebuireng Jombang have mastered and have skills that include: (1) Indonesian spelling, (2) sentence writing, (3) translation techniques, (4) translating Arabic text into Indonesian using good and correct Indonesian, and (5) being able to use computers in the process of translating Arabic text into good and correct Indonesian.